Empirical Model for Mobile Learning and their Factors. Case Study: Universities Located in the Urban City of Guadalajara, México - Juan Mejía Trejo; José Sánchez Gutiérrez; Guillermo Vázquez Ávila (Universidad de Guadalajara, 2015)
Information and communication technologies (ICT) are producing new and innovative teaching-learning processes. The research question we focused on is: Which is the empirical model and the factors for mobile learning at universities located within the Metropolitan Zone of Guadalajara, in Jalisco, México? Our research is grounded on a documentary study that chose variables used by specialists in m-learning using Analytic Hierarchy Process (AHP). The factors discovered were three: Technology (TECH); Contents Teaching-Learning Management and Styles (CTLMS); and Professor and Student Role (PSR). We used 13 dimensions and 60 variables. 20 professors and 800 students in social sciences courses participated in the study; they came from 7 universities located in the Urban City of Guadalajara, during 2013-2014 school cycles (24 months). We applied questionnaires and the data were analyzed by structural equations modeling (SEM), using EQS 6.1 software. The results suggest that there are 9/60 variables that have the most influence to improve the interaction with m-Learning model within the universities.